Experimental simulations of climate change induced mismatch in oak and larval development rates impact indicators of fitness in a declining woodland moth. Issue 6 (18th April 2021) - Senior, Vicki L.; Botham, Marc; Evans, Karl L.
Abstract : Consequences of climate change‐driven shifts in the relative timing of spring activities of interacting species are insufficiently understood, especially for insects. We use a controlled experiment which simulates a trophic mismatch scenario in which lepidopteran larvae predominately feed on older leaves due to foliage developing faster than larvae growth rates. As a case study our experiment uses Orthosia cerasi, which is a widespread but declining woodland moth whose UK declines appear to be driven by warming temperatures. In the control experiment larvae are fed young oak Quercus robur leaves (bud burst stages six and seven), whilst in the treatment newly emerged larvae are fed young leaves but then gradually transition to feed on older leaves (post bud burst stage seven). We assess impacts on duration of the larval stage, pupal size and overwintering duration and survival. Larvae in the phenological mismatch treatment had a longer larval period, and smaller and lighter pupae. Larval diet did not carry over to influence emergence dates as earlier pupation of control larvae was balanced by an equivalent increase in the duration of the pupal stage. Increased time spent as larvae could increase predation rates from avian predators, whilst slowing the seasonal decline in food availability for those bird species. Reduced pupal size and weight are indicators of lower fecundity in emerging adults. Notably, we find that adults emerging from the mismatch treatment exhibited greater rates of abnormal vestigial wing development, which is likely to further reduce fitness. Trophic mismatches in which caterpillars have reduced availability of young leaves may thus contribute to the population declines observed in many woodland moth species due to increased mortality at larval stages, and adverse effects of early life conditions that reduce the reproductive success of emerging adults.